Glue versus suture for mesh fixation in open inguinal hernia repair - S., Jeyakumar; Chitrambalam, Tharun Ganapathy; Chandrasekaran, Shruthi (International Surgery Journal, 2018)
Background: Inguinal hernia is the most common surgical problem presenting to the surgical OPD. Lichenstein’s tension free hernioplasty is the one of the first surgeries learnt by surgical residents. Pain after inguinal hernia surgery is found to be debilitating and alters the quality of life in several patients, which has been attributed to the traumatic fixation of the mesh with sutures. Hence this study, to compare traumatic and atraumatic methods of mesh fixation in inguinal hernia repair. The aim of this study was to compare suture fixation versus tissue glue fixation of the mesh in inguinal hernia repair. Objective was to compare the immediate and chronic post- operative pain, intra operative time and complications if any. Methods: This study was done in the General Surgery Department of SRM Hospital, Medical College and Research Centre, Kattangulathur after ethics committee clearance. It is a single blinded study conducted on 51 consenting patients and meeting the inclusion criteria from March 2016 to August 2017, of which 26 were selected for glue (N Butyl-2-Cyanoacrylate) fixation and 25 for suture fixation according to simple randomization. A note of the pain on VAS scale at various time intervals, operative time and any complications were also recorded was made. Results: Results developed using SPSS software show a significant difference in the intraoperative time by both methods, with glue taking a significantly lower time than sutures. A Significantly lower immediate and chronic postoperative pain is observed in the glue group. However, the complication rates in both the groups were found to be equal. Conclusion: It can thus be concluded from this study that tissue glue mesh fixation is superior to suture mesh fixation in open inguinal repair in terms of operative time, immediate and chronic post-operative time.